Analysis of torrefaction of big bluestem and mixed grass from the Conservation Reserve Program - Linnebur, Kyle Henry (Kansas State University, 2013)
Biomass torrefaction is an important preprocessing step in improving biomass quality, specifically in terms of physical properties and chemical composition. The objective of this research was to study effects of torrefaction as a pretreatment method on chemical and elemental compositions and thermal properties of Conservation Reserve Program (CRP) biomass. Most CRP grasslands are a mixture of native grasses, and in the state of Kansas, species including indiangrass, big bluestem, little bluestem, sideoats grama, and switchgrass comprise a majority of CRP grounds. Pure forms of big bluestem biomass were analyzed and compared with a mixture of the species that make up CRP lands. Two strategies for torrefaction were tested: one with a pre-dry step and one without. After torrefaction, big bluestem and CRP biomass showed an increase in energy density, making the biomass more attractive as a biofuel source than raw biomass. Big bluestem also showed slightly higher calorific values than that of CRP biomass. The torrefaction process had a significant effect on chemical composition and elemental composition of the biomass. Carbon content increased and oxygen content decreased as torrefaction temperature increased. Glucan and xylose decreased and lignin increased as torrefaction temperature increased. Pre-drying biomass before torrefaction is beneficial to torrefaction of biomass with high moisture content because moisture removal leads to less dry matter loss while maintaining the same calorific value.
Keywords: Torrefaction; Big bluestem; Conservation Reserve Program; Alternative Energy (0363); Energy (0791); Engineering, Agricultural (0539)